POST-TRAUMATIC STRESS DISORDER: DIAGNOSTIC UPDATES, NEUROBIOLOGICAL MECHANISMS, AND EVIDENCE-BASED INTERVENTIONS - Miranda Neto, José Jorge de; Macedo, Maria Luísa Miranda; Teixeira, Ana Luiza Freitas; Griebeler, Giovanna Lucilla Ramos (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2026)
Post-traumatic stress disorder (PTSD) is a prevalent and disabling psychiatric condition associated with significant functional impairment, reduced quality of life, and high rates of psychiatric comorbidity. Advances in diagnostic classification, neurobiological research, and therapeutic approaches have expanded understanding of PTSD; however, challenges remain in translating scientific knowledge into effective clinical practice.Objective: To provide an integrative and clinically oriented review of PTSD, synthesizing updated diagnostic frameworks, neurobiological mechanisms, and evidence-based pharmacological and psychotherapeutic interventions.Methods: A narrative review of the literature was conducted using PubMed, SciELO, and international clinical guidelines, prioritizing systematic reviews, meta-analyses, and key randomized controlled trials. Diagnostic criteria from DSM-5-TR and ICD-11 were examined alongside neurobiological models and treatment evidence. Results: PTSD is characterized by dysregulation of cortico-limbic circuits, alterations in stress-response systems, and abnormalities in multiple neurotransmitter pathways. Trauma-focused psychotherapies and first-line pharmacological treatments, including selective serotonin reuptake inhibitors and serotonin–noradrenaline reuptake inhibitors, constitute the core of evidence-based management. Emerging interventions, such as neuromodulation techniques and pharmacologically assisted psychotherapy, show promise in selected clinical contexts but require further empirical validation. Conclusion: PTSD should be conceptualized as a multidimensional disorder resulting from interactions between neurobiological vulnerability, traumatic exposure, and psychosocial factors. An integrative and multimodal treatment approach remains essential to optimizing clinical outcomes. By bridging diagnostic, neurobiological, and therapeutic perspectives, this review contributes to a comprehensive understanding of PTSD and highlights pathways for individualized psychiatric care and future research.